Morbidity profile and outcome of new-born admitted in sick newborn care units of Uttar Pradesh, India - Singh, Satya Prakash; Paliwal, Harish Chandra; Shekhar, Saket; Kushwaha, Poonam (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Reduction in child morbidity and mortality is result of upgradation of infrastructure and quality of public health care services. India alone accounts for 30% of the global neonatal deaths occur in India that occurs due to preventable cause. So, the aim of this study was to assess the pattern and status of neonatalmortality observed in SNCUs of Uttar Pradesh, India. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Descriptive study was conducted based on secondary data obtained from sick new born care units (SNCU) online database from 89 Government-supported SNCUs of Uttar Pradesh, from April 2014 to March 2016. Data obtained included age, weight, sex, diagnosis, and outcome. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. 22933 neonates admitted in SNCU were included in study with 14269 (62.2%) were males and 8664 (37.8%) females. Majority of the subject (20070; 87%) were in 0-5 days old age group. Most (72.5%) of admitted new-born improved and discharged. Low birth weight was significantly (χ2 = 1334.2, p<0.001) related with outcome. Birth asphyxia contributed to maximum (36.11%) number of deaths, followed by respiratory distress syndrome (25.21%), sepsis (15.38%), prematurity and extremely low birth weight (5.8%). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Improved antenatal care, improved access to health facility, timely referral of high-risk cases, capacity building, intensive interventional management can reduce neonatal mortality and its complications. Study also warrants, in-depth community-based qualitative study to identify gender-specific, equity issues.